A SURVEY ON THE SAFETY SYSTEM MATURITY LEVELS OF ELECTRONICS MANUFACTURERS IN SOUTH KOREA - Shim, JooYong; Park, Jeong Hwa; Lee, Jung Mo; Park, Dal Jae; Lim, Jae-Yong (Journal of Applied Engineering Science, 2021)
The main objective is to identify the level of advancement of safety systems in various levels of smart factories. Smart level verification systems are being implemented in Korea, but safety systems are not paying much attention to smart factory level checks. Using the checklist, nine Korean electronics manufacturing enterprises checked the level of safety system. The checklist consists of 142 items, can be divided into four dimensions (laws and certifications, safety designs and configurations at the facilities, safety devices and guards, and maintenance and training). As a result, a high-ranked enterprise in smart factory level showed excellence in the safety system maturity level as well. Compared to the level of the company’s smart factory, the level of advancement of safety systems has been confirmed to be lower.